Peace Education in New Democracies : A Case of Croatia - Čorkalo, Dinka (Array, 2002)
The contemporary society faces two parallel processes as a consequence of the end of cold war era. On the one hand, there is process of globalisation and cooperation among countries in order to establish rules for peaceful co-existence. In the same time, there are many crisis spots in the world and the collapse of communist regimes in Eastern Europe brought to light suppressed national identities and religious, ethnic and minority issues. In aforementioned countries there is no history and practice of looking at conflicts as a potential for social change, since it was defined as unacceptable and in most of them ethnic and minority issues were forbidden themes translated and viewed as &#8220 ; class struggle&#8221 ; . So, the goals of peace education in emerging new democracies are twofold: to accept conflicts as potential for social change and deal with them actively and constructively and to promote right to diversity as common interest in order to enable various national, ethnic and religious groups for living together peacefully. In post-conflict new democracies several segments or stages of peace education should be implemented following trucks of two basic educational principles: bottom-up and top down approach. Following bottom-up approach we could talk about several stages of peace education process, which should be developed. In our opinion these stages should include trauma healing, education for non-violent conflict resolution, education for mutual interdependence, tolerance and respect for diversity, education for social justice and human rights and education for democracy and civil society. On the more macro level, i. e. following top down approach, strong institutional support for all stages of peace education should be established. This kind of convergent action could accomplish the final goal of peace education: change of the state of mind.